"Distribution of Mitochondrial DNA Intergenic COII/tRNALYS 9 bp Deletion in Iranian Populations" - SA Alemohammad; DD Farhud; M Hooshmand; M Sanati; P Derakhshandeh-Peykar; SJ Imam; M Rahmani (Tehran University of Medical Sciences, 2003)
A 9 bp deletion between cytochrome oxidase subunit II and tRNA Lys genes in mitochondrial DNA, has proven to be an extremely informative marker for tracing population history. Using the PCR-PAGE and PCR-SSCP techniques in this study, 152 DNA samples collected from Iranian populations were screened for the 9 bp deletion. No deletion was observed. A length polymorphism, most probably a 9 bp triplication, was detected in one case. This observation provides further evidence for an ancient migration from Africa to India through Saudi Arabia, Iraq, Iran and Pakistan. It also supports the hypothesis, which suggested diffusion of Iranian farmers to India after agricultural revolution. The existence of 9 bp deletions in a background of haplogroup I in Mediterranean and its absence in Iran, suggests that there is no eastward diffusion of this marker and therefore this haplotype would not be too old. The presence of 9 bp triplication supports its multiple independent origins.